SELF EFFICACY, OPTIMISM FOR ADOLESCENT RESILIENCE - Dhiza Dian Harly; Riska Ahmad; Nurfarhanah; Rezki Hariko (RADJA PUBLIKA, 2023)
This study aims to empirically prove the relationship between self-efficacy, optimism and the resilience of adolescents living in orphanages. This study uses a correlational descriptive quantitative method. The research sample consisted of 98 orphanage youths, the sampling technique used was total side technique. The data collection instruments were self-efficacy questionnaires, optimism questionnaires, and resilience questionnaires and the collected data were then analyzed using multiple regression techniques. The results of multiple regression analysis showed (R) of 0.703 (F=46.318; p<0.05), which means that self-efficacy and optimism simultaneously play a role in resilience. The coefficient of determination is 0.494, meaning that the effective contribution of self-efficacy and optimism in explaining the resilience variance is 49.4%, and from the standardized beta value it is found that self-efficacy has a greater role in resilience with a value of 0.506 than optimism of 0.278. The conclusion of this study is that there is a significant role of self-efficacy and optimism for the resilience of adolescents living in the Shine Alfalah orphanage.